If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a(a + -3) + -7(a + -3) = 0 Reorder the terms: 5a(-3 + a) + -7(a + -3) = 0 (-3 * 5a + a * 5a) + -7(a + -3) = 0 (-15a + 5a2) + -7(a + -3) = 0 Reorder the terms: -15a + 5a2 + -7(-3 + a) = 0 -15a + 5a2 + (-3 * -7 + a * -7) = 0 -15a + 5a2 + (21 + -7a) = 0 Reorder the terms: 21 + -15a + -7a + 5a2 = 0 Combine like terms: -15a + -7a = -22a 21 + -22a + 5a2 = 0 Solving 21 + -22a + 5a2 = 0 Solving for variable 'a'. Factor a trinomial. (7 + -5a)(3 + -1a) = 0Subproblem 1
Set the factor '(7 + -5a)' equal to zero and attempt to solve: Simplifying 7 + -5a = 0 Solving 7 + -5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5a = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5a = 0 + -7 -5a = 0 + -7 Combine like terms: 0 + -7 = -7 -5a = -7 Divide each side by '-5'. a = 1.4 Simplifying a = 1.4Subproblem 2
Set the factor '(3 + -1a)' equal to zero and attempt to solve: Simplifying 3 + -1a = 0 Solving 3 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1a = 0 + -3 -1a = 0 + -3 Combine like terms: 0 + -3 = -3 -1a = -3 Divide each side by '-1'. a = 3 Simplifying a = 3Solution
a = {1.4, 3}
| 10x+10y=200 | | -4+6y=-12 | | 20.1=24.6+a(17.02) | | 4(3+2m)-6(-8x-3)= | | 1/2d-3=2 | | g-4g=-5 | | 20-k=9 | | (5x-20)=(4x) | | x=sqrt(4x+12) | | 0.3(x+20)-0.02(x-10)=-2.2 | | 20-k= | | f(x)=ln(8) | | 28x^2=3x+1 | | -(f+5)=-14 | | 10x-y=-23 | | f(x)=-x^2+3x+18 | | 5x-16=14-5y | | 21+x=13 | | 5.3+U=3.20-2.7 | | x+y+3z=13 | | 7n^2+22n+5=0 | | (3x-20)+(7x+30)+(2x+50)=180 | | 3x-8=5x-10 | | y^2+3-(y+1)(y+2)=0 | | 4+3p-1=8p+7-3p | | 1/2d+3=2 | | 6x+12y=77 | | -1.5x+-14.5=-31 | | -2(y-4)=20+2y-12 | | 24.6=29+a(14.51) | | (7/2+2*2)*10= | | 0.7n=-3.5 |